Effects of Non‐native Fish on Lacustrine Food Web Structure and Mercury Biomagnification along a Dissolved Organic Carbon Gradient. (1st September 2020) - Barst, Benjamin D.; Hudelson, Karista; Lescord, Gretchen L.; Santa‐Rios, Andrea; Basu, Niladri; Crémazy, Anne; Drevnick, Paul E.
Abstract: Although the introduction of non‐native fish species has been shown to alter trophic ecology in aquatic ecosystems, there has been limited research on how invasive species alter methylmercury (MeHg) biomagnification in lacustrine food webs. We sampled surface water and biota from 8 lakes in Quebec, Canada, spanning a range of dissolved organic carbon (DOC) concentrations (2.9–8.4 mg/L); 4 lakes were inhabited by native brook trout ( Salvelinus fontinalis ), and the remaining lakes contained brook trout and a non‐native fish, Allegheny pearl dace ( Margariscus margarita ). Periphyton, zooplankton, macroinvertebrates, and fish were analyzed for: 1) stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope ratios to delineate food webs, and 2) total Hg (THg) or MeHg. Compared with the brook trout from reference lakes, fish from invaded lakes had higher length‐standardized THg concentrations as well as a narrower dietary range and elevated trophic level, inferred from unadjusted δ 13 C and δ 15 N values, respectively. The rate of Hg biomagnification was similar across invaded and reference lakes, implying little effect of the invasive fish on the trophic transfer of MeHg. Despite differences in food web structure due to pearl dace invasion, DOC was the strongest predictor of brook trout THg levels for all lakes, suggesting that underlying environmental factors exerted a stronger influence on brook trout THg concentrations than the presence of a non‐native forage fish. Environ Toxicol Chem 2020;39:2196–2207. © 2020 SETAC